Anti-H Antibody Showing Agglutination in the Anti-Human Globulin Phase in a Korean Patient - Koh, Young Eun; Ryu, Geun Young; Kim, Yoon-ho; Jang, Mi-Ae; Yoon, Soo-young; Lim, Chae Seung (Annals of laboratory medicine, 2016)
KCI Citation Count: 1